Profil Perilaku Asertif pada Siswa Kelas IX dan Implikasinya bagi Bimbingan dan Konseling Pribadi Sosial di SMP Negeri 5 Kota Serang Tahun 2019/2020 - Endah Annastasya; Rahmawati; Raudah Zaimah Dalimunthe (Jurnal Multidisiplin Madani, 2022)
Communication is a way of interacting between individuals and very important in social life. Assertive behavior is communication behavior between individuals that involves aspects of honesty and openness of mind and feelings. Adolescence is a period of transition between childhood and adulthood which includes biological, cognitive, social and emotional changes. This study aims to determine the profile of assertive behavior and its implications for the personal social guidance and counseling program at SMP Negeri 5 Serang City. This research method is descriptive quantitative research with one variable, namely student assertive behavior. The research subjects were students who were sitting in class IX of SMP Negeri 5 Serang City. The population of this study amounted to 191 students with a sample of 131 students who were selected using the Nonprobality Sampling method which was determined using the Purpossive Sampling method. The results of this study are students have assertive behavior in the high category as many as 86 students (65.6%), the medium category as many as 45 students (34.4%), and the low category as many as 0 students.